Approaching the N = 82 shell closure with mass measurements of Ag and Cd isotopes - Breitenfeldt, Martin; Borgmann, Christopher; Audi, G.; Baruah, S.; Beck, D.; Blaum, Klaus; Böhm, Christine; Cakirli, R. B.; Casten, R. F.; Delahaye, P.; Dworschak, M.; George, S.; et al. (Physical review. C, Nuclear physics, 2010)
Mass measurements of neutron-rich Cd and Ag isotopes were performed with the Penning trap mass spectrometer ISOLTRAP. The masses of 112,114−124Ag and 114,120,122−124,126,128Cd, determined with relative uncertainties between 2×10−8 and 2×10−7, resulted in significant corrections and improvements of the mass surface. In particular, the mass of 124Ag was previously unknown. In addition, other masses that had to be inferred from Q values of nuclear decays and reactions have now been measured directly. The analysis includes various mass differences, namely the two-neutron separation energies, the applicability of the Garvey-Kelson relations, double differences of masses δVpn, which give empirical proton-neutron interaction strengths, as well as a comparison with recent microscopic calculations. The δVpn results reveal that for even-even nuclides around 132Sn the trends are similar to those in the 208Pb region.